Developing flipbooks based on local wisdom to improve elementary school teacher competence - Mika Andika; Ade Purna Nugraha; Delpiah Wahyuningsih (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2026)
The rapid advancement of digital technology requires elementary school teachers to develop innovative, interactive, and contextual teaching materials. State Elementary School 19 of Mendo Barat, limited digital literacy and a heavy reliance on conventional methods remain significant challenges. This community service initiative aimed to enhance the competence of 10 teachers at the school in developing interactive digital flipbooks with a focus on localization. The implementation utilized a collaborative-participatory approach, encompassing design training through Canva, intensive mentoring, and the deployment of the Flipsmart25 platform as a local digital repository. Evaluation results indicated a significant improvement in teacher competence: the average pre-test score for the managerial aspect rose from 2.1 to 4.3 in the post-test, while the socio-community aspect increased from 2.4 to 4.6. The primary output of this activity is a series of interactive digital flipbooks that integrate Bangka Belitung's local wisdom, now accessible through the Flipsmart25 application. This initiative successfully established a learning-sharing ecosystem that supports sustainable digital independence within the school.